Literature Review: Palliative Care in Intensive Care Units - Akhsaniati, Novi Dwi; Adiyanto, Bowo (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2024)
Palliative care is defined as care with an approach that improves the quality of life of patients and their families in dealing with problems associated with life-threatening illnesses. As many as 75% of patients treated in the intensive care unit experience unpleasant symptoms. Various studies have shown that palliative care can reduce symptoms caused by invasive procedures in intensive care units and can provide end-of-life care. Thus, assisting patients proactively, decision-making with families, prospects for continued care planning and possible scenarios for end-of-life decisions are essential in intensive care units (ICUs). The integration of palliative care is an important part of comprehensive critical patient care. Critical care providers are often asked to provide pain relief to critically ill patients, hold family meetings to clarify the goals of care, deliver bad news, or provide end-of-life care and care for critically ill patients while providing support to their loved ones. Most ICU patients who are unable to make decisions rely on their families or carers for clinical decision making. Decision making for cardiopulmonary resuscitation, cessation of life-sustaining treatment (LST), and provision of artificial nutrition and hydration should be based on the patient's willingness to discontinue LST, with the involvement of family members and the multidisciplinary team, ensuring that decisions are aligned with the patient's values and goals. The application of palliative care in ICU care can relieve symptoms experienced by patients and can reduce unnecessary invasive procedures. In its application, decision making in palliative care must be based on ethical principles and involve the patient's family, and the decisions made must also be in line with the wishes and values of the patient. The application of palliative care focuses on good symptom management to reduce patient suffering.